Nonsteroidal Anti-Inflammatory Drugs (NSAIDS) Induced Acute Kidney Injury (AKI): Patient Profile and Outcome in Bangladesh Armed Forces - Nessa, Azizun; Fakir, Md Amzad H (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: In military environment where musculoskeletal injury is more common, NSAIDs abuse and subsequent AKI carries a special risk. This study of NSAIDs induced AKI was carried out to highlight this issue. Objective: To find out the incidence, risk factors, diagnostic approach, clinical course, management and outcome of patients of Bangladesh Armed Forces. Methods: This longitudinal study was carried out in nephrology centre, combined military hospital (CMH) Dhaka from July 2010 to Jun 2013. Total 59 patients of NSAIDs induced AKI were included in this study. Any patient having pre existing renal pathology or chronic kidney disease was excluded from the study. Results: Total 59 patients were included in this study. Mean age of the patient was 36±7.12 yrs. Forty five patients (76.27%) took NSAIDs at their own and 14 patients (23.73%) were prescribed by physician. Fifty one patients (86.44%) took NSAIDs because of musculoskeletal pain. Dehydration due to physical exertion (30.50%), gastroenteritis (15.25%) and nil per os (NPO) (5.08%) were the common predisposing factors. Common symptoms were swelling of the body (40.67%), headache (32.20%), fatigue (27.11%) and vomiting (13.55%). Oedema was the most common sign (40.67%). Blood urea and serum creatinine were raised in all patients. Treatment includes drug withdrawl (100%), fluid resuscitation (86.44%), fluid restriction (61.01%), short course of steroid (13.55%) and haemodialysis (10.16%). Forty seven patients (79.66%) had complete recovery within two weeks of therapy whereas nine patients (15.25%) required more than two weeks to one month for complete recovery. Three patients (5.09%) developed chronic kidney disease (CKD). Conclusion: NSAIDs induced AKI carries a good prognosis with early diagnosis and proper management and it can be prevented by limiting the availability of over the counter drugs and creating awareness both in physicians and patients. Journal of Armed Forces Medical College Bangladesh Vol.10(2) 2014